2022
DOI: 10.3390/ijerph19127163
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Experiences of the COVID-19 Pandemic and School Closures and Implications for Mental Health, Peer Relationships and Learning: A Qualitative Study in South-West England

Abstract: The COVID-19 ‘lockdown’ and multiple school closures disrupted the daily lives and routines of the entire UK population. However, adolescents were likely particularly impacted by such measures due to this time being key for social and educational development. This qualitative study explored young people’s experiences of lockdowns and school closures. Fifteen secondary schools within south-west England were initially contacted and three schools participated in recruitment efforts. From December 2020 to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
2
39
2
Order By: Relevance
“…In addition to functioning in the family environment, relationships with the peer group are an important indicator of social functioning. Young people emphasize the value they place on direct social contact with close friends [ 72 ]. As the results of this study show, adolescents and young adults with ASD perceive the loss of social contact as difficult [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to functioning in the family environment, relationships with the peer group are an important indicator of social functioning. Young people emphasize the value they place on direct social contact with close friends [ 72 ]. As the results of this study show, adolescents and young adults with ASD perceive the loss of social contact as difficult [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested social connectedness as a central dimension in determining adolescent well-being and that the feelings of belonging and integration in the school social environment mediated the relationship between students' academic and social skills and dimensions of social connection, happiness, and optimism within well-being ( 20 , 21 ). Furthermore, other studies [e.g., ( 22 )] suggested that adolescents' low social connectedness within middle school social groups is positively associated with depressive and anxiety symptoms.…”
Section: Adolescents' Well-being: the Epoch Modelmentioning
confidence: 98%
“…A British study reported longitudinal increases in depressive symptoms but not anxiety symptoms in late childhood (age 7–11 years; Bignardi et al., 2020 ). However, other papers reported no change in internalizing symptoms (Achterberg et al., 2021 or a reduction in risk for anxiety in early adolescents (Widnall et al., 2020 ). There is still limited evidence of longitudinal changes in mental health from before the pandemic to during the COVID‐19 pandemic in a large, diverse sample spanning all of adolescence (age 9–18).…”
mentioning
confidence: 97%